Sex differences in the severity of neuropsychiatric symptoms and their relationship with clinico-demographic and psychosocial factors in patients with amnestic mild cognitive impairment and mild Alzheimer's disease. (3rd March 2020) - Inamura, Keisuke; Shinagawa, Shunichiro; Tsuneizumi, Yuri; Nagata, Tomoyuki; Tagai, Kenji; Nukariya, Kazutaka; Shigeta, Masahiro
Abstract: Objectives: We examined differences in the severity of neuropsychiatric symptoms (NPS) according to sex and identified NPS-related clinico-demographic and psychosocial factors among community-living patients with amnestic- mild cognitive impairment (a-MCI) or mild Alzheimer's disease (AD). Method: Overall, 111 patients (44 males, 67 females) with mild a-MCI (n = 64) or mild AD (n = 47) were included. We divided the patients according to sex and compared their clinico-demographic and psychosocial factors, explored the severity of NPS using the subscales from the Neuropsychiatric Inventory-Questionnaire (NPI-Q), and further identified variables related to NPS. Results : Significant differences in several clinico-demographic and psychosocial characteristics were observed between the sexes. The severity of delusions was higher among females (mean, 0.48; SD, 1.60) than males (mean, 0.23; SD, 1.07; p = .02), while the severity of irritability was higher among males (mean, 0.97; SD, 1.92) than females (mean, 0.49; SD, 1.40; p = .03). The severity of delusions among females was related to the duration of cognitive decline (B = 0.37, p = .03), while the severity of irritability among males was related to general cognition (B = -0.40, p = .003). Conclusion: The severity of NPS among patients with a-MCI or mild AD differed according to sex. We identified NPS-related clinico-demographic factors among these patients. Sex differences should be considered when determining the need for NPS interventions.